2022
DOI: 10.3389/fpls.2022.978304
|View full text |Cite
|
Sign up to set email alerts
|

Glycine betaine increases salt tolerance in maize (Zea mays L.) by regulating Na+ homeostasis

Abstract: Improving crop salt tolerance is an adaptive measure to climate change for meeting future food demands. Previous studies have reported that glycine betaine (GB) plays critical roles as an osmolyte in enhancing plant salt resistance. However, the mechanism underlying the GB regulating plant Na+ homeostasis during response to salinity is poorly understood. In this study, hydroponically cultured maize with 125 mM NaCl for inducing salinity stress was treated with 100 μM GB. We found that treatment with GB improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 65 publications
1
16
0
Order By: Relevance
“…GB has an excellent role in improving photosynthetic efficiency and antioxidant enzyme activity to mitigate salt-induced growth inhibition. Moreover, GB maintained the Na + /K + ratio mainly by plummeting the buildup of Na + in plants ( Zhu et al., 2022 ). GB reduces the membrane peroxidation and improves the photosynthesis and yield under stress conditions in soybean ( Khalid et al., 2022 ).…”
Section: Role Of Osmoprotectants In Salt Stress Tolerance In Soybean ...mentioning
confidence: 99%
See 1 more Smart Citation
“…GB has an excellent role in improving photosynthetic efficiency and antioxidant enzyme activity to mitigate salt-induced growth inhibition. Moreover, GB maintained the Na + /K + ratio mainly by plummeting the buildup of Na + in plants ( Zhu et al., 2022 ). GB reduces the membrane peroxidation and improves the photosynthesis and yield under stress conditions in soybean ( Khalid et al., 2022 ).…”
Section: Role Of Osmoprotectants In Salt Stress Tolerance In Soybean ...mentioning
confidence: 99%
“…GB treatment increased Na + efflux in leaf protoplasts and reduced the cellular distribution of Na + . Furthermore, GB improved the vacuolar activity of NHX and V type H + -ATPases genes to improve salt tolerance ( Zhu et al., 2022 ). A previous study reported that GB biosynthesis in plant tissues is highly energy intensive ( Bai et al., 2022 ).…”
Section: Role Of Osmoprotectants In Salt Stress Tolerance In Soybean ...mentioning
confidence: 99%
“…It also protects enzymes, proteins and other molecules involved in disease resistance (Papageorgiou and Murata, 1995; Lavanya and Amruthesh, 2017). Moreover, GB improves plant tolerance to stresses, including drought (Raza et al ., 2014), salinity (Hasanuzzaman et al ., 2014; Zhu et al ., 2022) and heavy metals (Ahmad et al ., 2020). Lavanya and Amruthesh (2017) reported that GB has effectively controlled the downy mildew disease affecting pearl millet ( Pennisetum glaucum L.).…”
Section: Introductionmentioning
confidence: 99%
“…Trehalose is a nonreducing diglucoside elevated in plants under salt stress, probably protecting protein and membrane structures and regulating the antioxidant systems to ameliorate ROS scavenging, and trehalose-6-phosphate synthase (TPS) is one of the key enzymes in terms of trehalose biosynthesis [ 33 ]. Moreover, in maize, glycine betaine [ 34 , 35 ], trehalose [ 36 ], ascorbate–proline–glutathione [ 37 ], and phosphate [ 28 ], are applied to counter salt stress, which is favorable for the maintenance of Na + /K + balance and improvements in antioxidant defense. Recently, single or combined analyses of genomes [ 38 ], transcriptomes [ 34 , 39 ], proteomes [ 40 , 41 , 42 , 43 ], and metabolomes [ 44 , 45 ] and a genome-wide association study (GWAS) revealed differential expression genes, small RNAs, and regulatory networks in plants under salt stress [ 46 , 47 , 48 ], which provided valuable information to understand the mechanism of salt response.…”
Section: Introductionmentioning
confidence: 99%